A novel null allele, HLA‐DPA1*01:35N in a European American Male from Pennsylvania, USA. (10th June 2020) - Fisher, Carolyn; Casey, Heather; Kumer, Lorie; Tyler, Jennifer; Shike, Hiroko
Abstract : A non‐sense mutation in either DPA1*01:03:01:02 or DPA1*01:03:01:05/01:03:01:15 results in the novel allele, HLA‐DPA1*01:35N .